Fodor's Vienna & the best of Austria 2024 : [with Salzburg & skiing in the Alps] - Johnston, Raymond (Travel writer); Mawson, Emily Rose; Meyer, Jacy; Reaney, Joseph; Williams, Timothy (Fodor's travel guides., 2024)
"Whether you want to explore Vienna's elegant palaces and concert halls, ski the Austrian Alps, or soak in the charms of Salzburg's classical music scene, the local Fodor's travel experts in Vienna are here to help! Fodor's Vienna & the Best of Austria guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos." --